2001
DOI: 10.1016/s0736-0266(00)00066-8
|View full text |Cite
|
Sign up to set email alerts
|

Chondrocyte necrosis and apoptosis in impact damaged articular cartilage

Abstract: A decrease in chondrocyte numbers is one characteristic of osteoarthritic cartilage. This decrease may be the result of apoptosis or other forms of cell death induced by mechanical damage. Furthermore, cell death may contribute to the structural and metabolic changes found in osteoarthritic cartilage. Therefore, we investigated cell viability and the mode of cell death in cartilage subjected to an increasing severity of impact loads expected to cause compositional damage and osteoarthritic-like metabolic alter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
177
0
3

Year Published

2002
2002
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 201 publications
(192 citation statements)
references
References 19 publications
12
177
0
3
Order By: Relevance
“…As a result, some cells undergo necrotic death in the short term, whereas the remaining traumatized cells may enter an apoptotic pathway later. 34 Additionally, a previous study by Natoli and Athanasiou 5 suggests that less necrosis may lead to decreased apoptosis by preventing the release of apoptotic initiators from necrotic cells, thereby preventing further death at later time points. Apoptotic initiators and other intracellular signals may be involved in the spreading of cell death through the cartilage matrix.…”
mentioning
confidence: 98%
“…As a result, some cells undergo necrotic death in the short term, whereas the remaining traumatized cells may enter an apoptotic pathway later. 34 Additionally, a previous study by Natoli and Athanasiou 5 suggests that less necrosis may lead to decreased apoptosis by preventing the release of apoptotic initiators from necrotic cells, thereby preventing further death at later time points. Apoptotic initiators and other intracellular signals may be involved in the spreading of cell death through the cartilage matrix.…”
mentioning
confidence: 98%
“…Mechanical loads applied in vitro range from single compressions of up to 50% strain (12)(13)(14)(15)(16)(17) to large-amplitude cyclic compression at varying frequencies (ϳ0.05-0.3 Hz) for up to 2 hours (18)(19)(20)(21). Injurious mechanical compression of cartilage in vitro can damage the extracellular matrix (ECM), leading to increased water content (12,16,18,22), decreased stiffness (12,22), increased hydraulic permeability (20), loss of glycosaminoglycan (GAG) to the culture medium (12)(13)(14)(15)17,20,22,23), loss of collagen to the medium (20), and temporary denaturation of collagen in the tissue (16,18,20,21).…”
mentioning
confidence: 99%
“…Injurious mechanical compression of cartilage in vitro can damage the extracellular matrix (ECM), leading to increased water content (12,16,18,22), decreased stiffness (12,22), increased hydraulic permeability (20), loss of glycosaminoglycan (GAG) to the culture medium (12)(13)(14)(15)17,20,22,23), loss of collagen to the medium (20), and temporary denaturation of collagen in the tissue (16,18,20,21). In addition, injurious mechanical compression can lead to cell death by both apoptosis and necrosis (14,16,19,(21)(22)(23), as well as decreased matrix biosynthesis rates in the remaining viable cells after injury (12).…”
mentioning
confidence: 99%
“…Necrosis was observed 2 h after cessation of loading, whereas apoptosis (TUNEL-positive cells) was not significant until 48 or more hours after loading stopped. Apoptosis was verified in some cells using transmission electron microscopy [3]. A study that induced osteochondral wounding of a joint also found significant percentages of necrotic and apoptotic cells in the tissue [29].…”
Section: Resultsmentioning
confidence: 92%